Os motivos da relação entre orientação para aprendizagem e performance - Vieira, Márcia Horowitz (2015)
The choice of the strategic orientation to follow is essential to the organizational success. Learning oriented organizations are guided by a shared vision that is focused on the creation and use of knowledge in order to enhance competitive advantage. These firms will monitor competitors’ behaviors to understand and learn about their strengths and weaknesses, and to transform their own behaviors, processes and attitudes in a progressive and long-term way, developing organizational capabilities that will stimulate employees to question procedures and norms related to market information and the way this organization should behave before the market. As we understand that this strategic orientation offers a unique distinction in adaptation and reorganization of processes, it is possible to perceive the existence of the relationship between this orientation and organizational performance. In the literature, the relation between learning orientation and performance is supported in different ways and is, essentially, seen as needed in order to reach superior performance. In this way, the present study objective was to comprehend the reasons of the relationship between learning orientation and organizational performance, considering the existence of different configurations of this relation and possible factors that influence the results. In addition to this, this research tried to fulfill a theoretical gap, as until that moment, there were no qualitative studies found about this theme. Therefore, through a qualitative and exploratory research, a wide theoretical survey was first made followed by in-depth interviews with academic and market specialists. Since the data analysis, five final categories and twenty-two subcategories were formed to represent the motives of the relationship between learning orientation and performance that were extracted from the data collected. Among the main results, it was possible to conclude that several mediators, known as the reasons of the relationship, were recognized either in the theory as in the perception of the academic and in market specialists. However, it was also identified new variables, not found in the theory studied, extracted from the data collection and data analysis. At last, this research, presents academic and management implications about the motives that lead learning orientation organizations to reach superior performance, besides indicating this research limitations and suggestions for future studies.